High-affinity binding of granulocyte-macrophage colony-stimulating factor to normal and leukemic human myeloid cells. - Gasson, J C (1986)
Purified natural and biosynthetic (recombinant) human granulocyte-macrophage colony-stimulating factor (GM-CSF) stimulate colony formation by myeloid progenitor cells and enhance the function of mature neutrophils. Both of these actions occur at concentrations between 1 and 100 pM, with half-maximal stimulation at 10-20 pM. We have examined specific binding of 125I-labeled GM-CSF to responsive target cells in this range of concentrations. The results show a low number (50-250) of high-affinity (15-30 pM) binding sites on GM-CSF-responsive leukemic cells (KG-1, HL-60), as well as on peripheral blood neutrophils from normal donors. This high-affinity binding component was absent from unresponsive cell lines (KG-1a, K562). These results suggest that this binding site mediates the biological activities of GM-CSF on both proliferation and function of myeloid cells.